Bioethical Aspects of the Criminal Law Regulation of the Necrophilia in the Republic of Croatia - Janeš, Luka; Nedić, Tomislav (Glasnik Advokatske komore Vojvodine, 2020)
Necrophilia is one of the most tabooistic segments of the psychopathological, but also of the law categories, whereat issues of acts against the (deceased) human body and its desecration, but also the phenomena of life and death per se, are coming to the fore. This paper seeks to contribute to the evaluation of the certain problematic law and (bio)ethical segments related to the given, primarily by using a case law method, formal-logical legal method, as well as the method of linguistic interpretation of law, as an argumentative aid for the analysis of the criminal law regulation of the necrophilia. Also, in the mentioned discourse will be implemented a bioethical sensibilty – the intentional subject attribute of integrative bioethics, for the purpose of orientation and emphasiz of the responsibility towards a person's life as the fundamental deontological paradigm of the certain law procedures.
Keywords: necrophilia, the offense of violating the peace of the deceased person, desecration of the body, personality disorder, bioethical sensibility, Körper/Leib